Pentahelıx Collaboratıon Strategy In The Development Of Lodtunduh Tourısm Vıllage, Ubud Dıstrıct, Gıanyar Dıstrıct - Ni Wayan Gita Sadhana Savitri; Ni Putu Ratna Sari; I Nyoman Darma Putra (Cita Konsultindo Research Center, 2024)
Tourism village provides various benefits, from reducing urbanization to improving the living standards of local communities. However, developing tourism village is challenging because it follows the character of village that experience slow growth. Research focusing on the pentahelix collaboration strategy to developing tourism village.This research uses a qualitative approach with data collection techniques such as observation, interviews, and literature studies. Informants were determined through purposive sampling involving pentahelix actors. The instruments research such as interview guidelines, cameras, and recording devices. Data is analyzed using NVivo software and SWOT analysis to produce a pentahelix collaboration strategy for the development of tourism village.This research concludes three points: first, the quality and active participation of the community are the main obstacles, so the village government builds networks, comparative studies and increases local community participation as a solution to these obstacles. Second, the roles of other pentahelix actors such as the government, academics, business, and media are not optimal. Third, Lodtunduh Tourism Village utilizes its natural, cultural, and artificial potentials, as well as its location as an entry point to Ubud, to develop strategies using SWOT analysis. This analysis resulted in 12 strategies focusing on human resource strengthening, promotion, creation of tour packages, expanding networks, utilizing digital platforms, and strengthening regulations.Based on the research results, several suggestions can be considered for the development of tourism village, including the intensive implementation of local human resource capacity building, considering that the community is the spearhead in the development of tourism village. It is also important to create a communication network forum that can be easily accessed by tourism village managers.